2014
DOI: 10.1016/j.bbr.2014.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Diet-induced obesity attenuates cytokine production following an immune challenge

Abstract: Obesity increases susceptibility for numerous diseases and neurological disorders including cardiovascular disease, metabolic syndrome, and dementia. One factor that may contribute to the increased risk for these conditions is the development of chronic inflammation. The current study evaluated whether diet-induced obesity (DIO) affects cognitive performance by increasing neuroinflammation and prolonging the behavioral and inflammatory response to an immune challenge. Adult male C57BL/6J mice were fed a high-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 42 publications
2
18
1
Order By: Relevance
“…To date, the existing literature on the effects of DIO on the behavioral response to an immune challenge has been limited to sickness behavior and has shown mixed results. DIO was reported to prolong the LPS-induced suppression of social behavior in rats, but had no effect on the LPS-induced reductions in locomotor behavior [17, 22]. In agreement we found that LPS administration reduced swim speed on day 1 of testing in both the DIO and control diet mice.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…To date, the existing literature on the effects of DIO on the behavioral response to an immune challenge has been limited to sickness behavior and has shown mixed results. DIO was reported to prolong the LPS-induced suppression of social behavior in rats, but had no effect on the LPS-induced reductions in locomotor behavior [17, 22]. In agreement we found that LPS administration reduced swim speed on day 1 of testing in both the DIO and control diet mice.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, macrophages from DIO animals show reduced interleukin-1β (IL-1β), TNF-α, nuclear factor-κB (NF-κB), Toll-like receptor-4 (TLR-4) and inducible nitric oxide synthase (iNOS) levels following an immune challenge when compared to macrophages from control diet animals [1316]. In addition, we found attenuated levels of IL-6 in the cortex of DIO males mice following LPS administration [17]. Presently, the reason for these divergent findings is unknown, but variations in the experimental procedure including differences in the animal’s age, species, timing of tissue sampling, as well as the type and duration of the diet, among other factors, likely contribute to these differences.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of obesity in modulating the response to infection has been mostly studied in rodent models and has been recently reviewed [44 ]. Despite some studies reporting a decrease or no change in LPS-induced fever, peripheral inflammatory response or behavioral manifestations in obese rodents in comparison to their lean controls [45], a majority of the reports suggest an increase and/or prolongation of the immune response induced by LPS [46 ,47 ]. In addition, the few studies that have been conducted in humans using ex vivo protocols also suggest obesity to be associated with an intensified response to an inflammatory challenge.…”
Section: Current Opinion In Pharmacologymentioning
confidence: 99%